2005
DOI: 10.1103/physrevb.72.165421
|View full text |Cite
|
Sign up to set email alerts
|

Resonant backward scattering of light by a subwavelength metallic slit with two open sides

Abstract: The backward scattering of TM-polarized light by a two-side-open subwavelength slit in a metal film is analyzed. We show that the reflection coefficient versus wavelength possesses a Fabry-Perotlike dependence that is similar to the anomalous behavior of transmission reported in the study [Y. Takakura, Phys. Rev. Lett. 86, 5601 (2001)]. The open slit totally reflects the light at the near-to-resonance wavelengths. In addition, we show that the interference of incident and resonantly backward-scattered light pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…Here it is interesting to mention that a cavity in the shape of a ten nanometer-sized slit in a conducting metal film also demonstrates optical properties which are inherent to a Fabry-Pérot resonator/interferometer [30][31][32]. Fig.…”
Section: A Fabry-pérot Interferometer With An Ultra-thin Spacer Layermentioning
confidence: 97%
“…Here it is interesting to mention that a cavity in the shape of a ten nanometer-sized slit in a conducting metal film also demonstrates optical properties which are inherent to a Fabry-Pérot resonator/interferometer [30][31][32]. Fig.…”
Section: A Fabry-pérot Interferometer With An Ultra-thin Spacer Layermentioning
confidence: 97%
“…Inside the slit, the maxima are slightly shifted from that of the cw [8]. The effect is caused by the internal reflection of the pulse at the slit entrance and exit.…”
mentioning
confidence: 97%
“…Experiments as well as computations were performed to investigate this problem for various parameters: pulse length, object shapes and sizes, etc. [3][4][5][6][7][8][9][10][11][12][13][14][15]. It was shown that the scattering process alters the pulse shape and spectrum, resulting in various effects such as pulse broadening, compression, time delay or advancement, and spectral shifts.…”
mentioning
confidence: 99%
See 2 more Smart Citations